Diagnostic Accuracy of Chest Radiography Versus Lung Ultrasound in Pediatric Pneumonia: A Comparative Study - Zainab Zahid, Sobia Shabbir, Rameeka Ahmad, Sarah Ghias, Almitra Farnaz, Shamshad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Community-acquired pneumonia remains a leading cause of childhood morbidity and mortality. Chest radiography (CXR), the conventional imaging standard, exposes children to ionizing radiation and may miss small or peripheral lesions. Lung ultrasound (LUS) offers a rapid, radiation‐free alternative at the bedside. Objective: To compare the diagnostic accuracy of LUS versus CXR for community‐acquired pneumonia in children aged one month to five years. Methods: In this comparative study conducted from June 2022 to June 2023 at Doctors Hospital (Lahore), Faisalabad Teaching Hospital, and Avicenna Hospital (Lahore), 100 children with clinical signs of pneumonia underwent both CXR and LUS within 24 hours of presentation. Radiographs were independently interpreted by two pediatric radiologists, and ultrasound examinations were performed by a trained pediatrician over twelve standardized lung zones. A blinded panel of pediatric infectious disease specialists established the reference diagnosis using World Health Organization criteria, elevated biomarkers (CRP > 20 mg/L or leukocytosis ≥ 15 × 10⁹/L), and seven‐day clinical follow‐up. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for each modality. Results: Seventy‐eight children (78 %) were confirmed to have bacterial pneumonia. LUS demonstrated a sensitivity of 96.2 %, specificity of 90.9 %, PPV of 97.4 %, and NPV of 87.0 %. In comparison, CXR yielded a sensitivity of 82.1 %, specificity of 72.7 %, PPV of 91.4 %, and NPV of 53.3 %. Differences in sensitivity (∆14.1 %, p < 0.001) and specificity (∆18.2 %, p = 0.02) favored LUS. Conclusion: Bedside lung ultrasound significantly outperforms chest radiography for diagnosing pediatric pneumonia. Its rapid, radiation‐free nature and high diagnostic accuracy support its adoption as a first‐line imaging modality to improve patient care and optimize resource utilization. Keywords: pediatric pneumonia; lung ultrasound; chest radiography; diagnostic accuracy; ultrasound.